Fundamentals of slit-lamp biomicroscopy - Farrell, Thomas A.; Alward, Wallace L. M.; Verdick, Randall E.; American Academy of Ophthalmology (San Francisso : America Academic of Opthalmology, 1994)
Provides an introduction to biomicroscopy using the Haag-Streit 900. Slit-lamp images and labeled graphics highlight maneuvers and special techniques that enhance the examination. Demonstrates the skills required to master this complex machine and illustrates what will be seen by the examiner. Includes a description of the Zeiss 30 SL.
Videorecording is available at Koleksi Media Perpustakaan HUKM
Thoams A. Farrell, W.L.M. Alward, Randall E. Verdick
Keywords: Microscopy -- methods -- videocassettes; Microscopy -- instrumentation -- videocassettes; Eye Diseases -- diagnosis -- videocassettes; Gonioscopy -- methods -- videocassettes